A minimal region of the HSP90AB1 promoter is suitable for ubiquitous expression in different somatic tissues with applicability for gene therapy - Mielcarek, Michal; Isalan, Mark (Frontiers in Molecular Biosciences, 2023)
Huntington’s disease (HD) is a multi-tissue failure disorder for which there is no cure. We have previously shown an effective therapeutic approach limited mainly to the central nervous system, based on a synthetic zinc finger (ZF) transcription repressor gene therapy, but it would be important to target other tissues as well. In this study, we identify a novel minimal HSP90AB1 promoter region that can efficiently control expression not only in the CNS but also in other affected HD tissues. This promoter-enhancer is effective in driving expression of ZF therapeutic molecules in both HD skeletal muscles and the heart, in the symptomatic R6/1 mouse model. Moreover, for the first time we show that ZF molecules repressing mutant HTT reverse transcriptional pathological remodelling in HD hearts. We conclude that this HSP90AB1 minimal promoter may be used to target multiple HD organs with therapeutic genes. The new promoter has the potential to be added to the portfolio of gene therapy promoters, for use where ubiquitous expression is needed.